Reinforcement Effects of Inorganic Nanoparticles for Double‐Network Hydrogels. Issue 12 (12th August 2015) - Zhai, Yunge; Duan, Hongdong; Meng, Xia; Cai, Kun; Liu, Yu; Lucia, Lucian
Abstract: This paper aims at investigating reinforcement effects and mechanisms of four kinds of nanoparticles (SiO2, hectorite, Al2 O3 and TiO2 ) for double‐network hydrogels. Mechanical tests were conducted to determine optimal contents and advantages of those nanoparticles in improving strength or strechability. The results showed that the hydrogels with Al2 O3 showed a tensile stress of 0.33 MPa, the compressive stress of 3.38 MPa and high fracture energy of 1117 J · m −2, while the hydrogels with hectorite achieved a strain ratio of 2280% and better elastic modulus of 170.2 kPa. The reinforcement mechanisms were discussed in terms of morphologies, swelling behaviors and dynamic mechanical properties. Moreover, a cell culture test was applied to prove these nanocomposite hydrogels were non‐poisonous to living cells. Abstract : Different inorganic nanoparticles are applied to enhance the mechanical properties of double‐network hydrogels. The layered and thin nano‐hectorite hydrogels have the best stretch ratio, while the globular nano‐Al2 O3 hydrogels have an outstanding compressive stress. The enhancement mechanism of these different nanoparticles is revealed in terms of morphological determination and other mechanical analyses.